Ett svenskt dialektlexikon i startgroparna - Hallén, Karin; Thelin, Eva (Nordiske Studier i Leksikografi, 2006)
A Swedish dialect dictionary ready to start. The project Swedish Dialect Dictionary has been in progress at the Institute for Dialectology, Onomastics and Folklore Research in Uppsala since 2003. People interested in dialects constitute the target group and the dictionary will be published in book form. A timescale of ten years and a limit of 1200 pages are some preliminary constraints. The collections of dialect words at the Institute are considered a sufficient basis in spite of a slightly uneven geographical distribution. Selection criteria are discussed, among others, that the dialect words should be drawn from at least ten independent sources or derive from three provinces. Besides the usual items of information on pronunciation, meaning etc., the microstructure of the dictionary entries contains the geographical distribution of the occurrences. The need for increased resources if the project is to be completed within the time stated is emphasised.